Pelatihan Senam Sehat dan Pengukuran Komposisi Tubuh untuk Meningkatkan Wellness Fisik Lansia - Muya Barida; Widyastuti, Dian Ari; Hartini, Sri; Partini, Siti; Arikunto, Suharsimi; Muarifah, Alif; Martaningsih, S.T.; Miksa, Murein (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Seniors need to exercise to stay healthy and fit. This community service program aims to encourage seniors to practice a series of healthy exercises that are easy for them to implement in their daily activities and also to measure their body composition, so that they are more enthusiastic about improving their physical wellness. This healthy exercise training for seniors focuses on the composition of their muscles, fat, and bones. Body composition measurements use a Smart BMI Scale that can measure body weight, body fat, water content, muscle mass, physical rating, calorie needs, cell age, bone density, abdominal fat, fat content, bone mass, and posture. The results showed that most seniors had difficulty following the trainer's instructions during healthy exercises due to stiff bodies and a lack of structured movements. In addition, some seniors' body composition was less than ideal. This exercise made seniors happier and more energetic. Through these two activities, seniors committed to implementing light exercise in their daily lives and maintaining body composition by paying attention to diet, regulating mindsets, and improving movement patterns.